Peningkatan Kinerja dan Kerjasama Tim Peneliti Depdagri dan Daerah dalam Otonomi Daerah - Supratikta, Hadi (Research and Development Agency Ministry of Home Affairs, 2009)
The Research and Development Agency of the Ministry of Home Affairs as a professional and academic institution, must be able to interact and cooperate with various parties, with government and non-government agencies, both at the center and in the regions. In this regard, this study attempts to reveal the strategic role of the Research and Development Agency which must improve the performance and cooperation of the Research Team of the Ministry of Home Affairs and the Regions in regional autonomy. With a descriptive method of accessing data from several primary data sources, work experience, interviews, literature studies, handbooks, and others, this study uses the theory of Problem Solving and Decision Making (PMPK) and the theory of Integrated Work Patterns. Improving the performance and cooperation of the Central Research Team at the Ministry of Home Affairs and the Regions in strengthening regional autonomy can be successful effectively and efficiently, by understanding actual problems that are closely related to the main tasks and functions of the Research and Development Agency. The strategy must be able to identify the causes of problems. Including the main and specific problems, determining priority efforts to be carried out and programmed as an effort to solve existing problems. Allocating any costs needed to carry out competitive grant research, as well as complete details of work allocation. It must describe the network of work, who does what, who is responsible to whom, who works with whom and when to do what.